The costs of using night roosts for migrating whimbrels. (27th January 2021) - Watts, Bryan D.; Smith, Fletcher M.; Hines, Chance; Duval, Laura; Hamilton, Diana J.; Keyes, Tim; Paquet, Julie; Pirie‐Dominix, Lisa; Rausch, Jennie; Truitt, Barry; Winn, Brad; Woodard, Paul
Abstract : Migrant shorebirds operate within a series of landscapes and must adjust their daily activities to achieve seasonal time and energy objectives. Night roosts are essential landscape elements that provide safety from predators for many shorebird species. What costs migrants incur to use night roosts and how these costs vary across staging sites are poorly understood. We tracked 42 adult whimbrels Numenius phaeopus with satellite transmitters and used night locations to delineate 39 night roosts during spring and fall migration. We used daytime locations to measure round‐trip commuting distances between night roosts and foraging areas and estimated daily commuting costs including distance, time and metabolic energy expenditure. We identified night roosts on offshore islands (n = 20) and onshore locations including along habitat edges (n = 13) and on topographic highs within extensive marshes (n = 6). Mean daily commuting costs varied between roosts. Whimbrels took 3.9–52.1 min (median = 15.2) to fly 3.1–42.2 km (median = 12.3) which costs 6.1–82.4 kj (median = 22.3) in lean mass energy expenditure and 8.1–109.2 kj (median = 31.5) in leaving mass energy. Birds using offshore roosts had twice the commuting distance and associated costs compared to those using onshore roosts. The contribution of commuting costs to the premigratory energy budget ranged from 1.5 to 18.8% with costs for nearly 30% of roosts exceeding 10%. Commuting costs to and from night roosts appear to be biologically relevant within some staging sites and should be considered among other constraints faced by migrants during stopover periods when food or time is limiting.